Deep‐Subwavelength Optical Spin Textures in Volume Plasmon Polaritons with Hyperbolic Metamaterials. Issue 4 (12th December 2022) - Gan, Shuaiwen; Shi, Peng; Yang, Aiping; Lin, Min; Du, Luping; Yuan, Xiaocong
Abstract: Hyperbolic metamaterials can support extremely high‐ k wavevectors, also known as volume plasmon polaritons, with highly directional propagation and light confinement to deep‐subwavelength scales. The number of high‐ k modes has an inverse relationship with the overall thickness of hyperbolic metamaterials. Here, the optical spin textures from high‐ k mode polaritons on the surface of silica–silver multilayer hyperbolic metamaterials are studied. The results demonstrate that with an increase in the overall thickness, the spin texture changes from a twisted structure to a Néel‐type photonic skyrmion, due to the decrease in the number of high‐ k modes. Moreover, the size of a single photonic skyrmion is less than 1/2 of the light wavelength, and the full width at half maximum of the spin angular momentum is less than 1/9 of the light wavelength. This work is expected to facilitate new applications of hyperbolic metamaterials, such as spin‐dependent excitation and detection devices at the deep‐subwavelength level. Abstract : Spin vector structure of the volume plasmon polaritons vortex forms the deeply subwavelength photonics skyrmion on the surface of silica–silver multilayer hyperbolic metamaterials. By increasing the number of periods of the hyperbolic metamaterials, the structure of the spin vector changes from a twisted photonic skyrmion to a Néel‐type photonic skyrmion.